Metodologia para melhoria de desempenho de sistema de esgotamento sanitário de condomínios: o caso do condomínio Parque São José do Rio Negro - Monteiro, Luiz Fernando Vasconcelos (Brasil, 2022)
It is natural that installed infrastructures undergo modifications by human action and deterioration of materials over time, losing quality in performance, justifying characterization studies, evaluation, monitoring and diagnosis that help in the identification of inadequacies and in the proposition of interventions for their improvement. In this context, the ‘Condomínio Parque São José do Rio Negro’ (CPSJRN), located at ‘Avenida Jornalista Umberto Calderaro Filho’, Adrianópolis area in the city of Manaus / AM, has been undergoing actions to adapt the sewage system in the last seven years, including a sewage treatment plant (ETE), meeting the requirements of environmental legislation. On the other hand, it was observed that the sewage system suffers from large flow rates in rainy periods. Then, the present study aimed to: identify, quantify and characterize nonconformities in the system and in accessory devices, showing their causes and consequences; propose interventions for its elimination and methodology that can be replicated to improve the performance of the CPSJRN sewage system. For this, there were carried out research of theoretical references, on-site surveys - direct observation, semi-structured interviews, photographic and video records, as well as data systematization using text software, spreadsheets, and computer graphics. 20 (twenty) points of contributions were identified in the sewage system not foreseen in the ETE adequacy project, which 11 (eleven) of them came from buildings/surrounding areas, representing 10% (ten percent) of the project flow rate, and 9 (nine) from the intersection with elements of the rain drainage system, resulting in an increase in flow rate on rainy days up to 200 (two hundred) times greater than the project flow rate. It was also observed that the system suffered natural degradation over the years, as a result of: maintenance and conservation actions (or lack of them); interventions to incorporate new functionalities in sanitary environments or even the creation of new ones, some without considering technological developments and scientific knowledge; unplanned contributions either by the intersection with the drainage system or by effluents from buildings and surrounding areas. All of them with direct implications in the system and overtaxing the condominium, besides establishing a forced condominium between the condominium building Parque São José do Rio Negro and areas/buildings of the surrounding. Therefore, it is recommended to this condominium some detailed studies: about the legal aspects of the contributions of the surroundings to propose alternatives that minimize or eliminate negative impacts; about the rain drainage network for the projection of interventions that ensure its separation from the sewage system (separate sewage system); adjustments in grease trap; and action plan for its feasibility. As a consequence, to improve the performance of sewage systems of condominiums under similar conditions, the following procedures are suggested: characterization, diagnosis and critical evaluation of the enterprise and its sewage and rain drainage systems (components, non-conformities and their respective causes, measuring impacts, positive or negative, in the system and treatment unit); identification of the construction period and changes in laws, current regulations and technical recommendations after its construction; proposal of intervention strategies in a feasible plan of action from a technical and economic point of view.